International Relations Theory - Daddow, Oliver (SAGE Publications, Ltd. (UK), 2017)
With chapters on all the major theories of international relations, accompanied by contemporary examples from popular culture, film and literature, this Third Edition is the ideal introduction to the key perspectives in the field. Key features: 30% new content, with all chapters revised and updated  Useful learning features including further reading, ′questions to ponder′, ′common pitfalls′ and ′taking it further′ boxes, to help you extend your thinking beyond the classroom    Invaluable chapters on getting the best out of your knowledge of International Relations Theory in essays and exams, including real life examples of best practice.